Language anxiety and coping strategies :students of English generic courses in UNIMAS - Tang, Siew Kit. (Universiti Malaysia Sarawak, UNIMAS, 2008)
This study investigated the language anxiety level and coping strategies among the UNIMAS students of English generic courses. This study aimed to identify the most experienced anxiety type, the anxiety levels, and the most frequently used coping strategy. This study set out to find whether gender influenced the anxiety levels, and also whether the anxiety levels influence d the choices of the cop ing strategies. A self - rating questionnaire was used to probe levels of agreement pertaining language anxiety and coping strategies of 338 respondents , who were students from two classes for each of the seven English generic courses. The result showed that Communication Apprehension was the most experienced anxiety type whereas Preparation was the most frequently used coping strategy. 53.3% of the sample population came under low anxiety group. The result revealed that variable gender did not influence the anxiety levels of 114 males and 224 females. Both genders had the highest number in the low anxiety level, and the least number in the high anxiety level. However, the different generic courses influenced the anxiety levels of the students. There was no si gnificant difference between the choices of coping strategies among the students with different anxiety level. Active coping strategies were preferred than emotion - related coping strategies by the respondents. The current study is unable to provide specifi c information about what language tasks had triggered the anxiety feeling. Therefore, f uture undertakings are suggested to focus on identifying language tasks that make students anxious to a degree that prohibits them from learning effectively.